The Relationship between Perceived Risk and Online Purchase Intention - Salim, Siti Aisyah; Bahanan, Nur Azyyati (Research in Management of Technology and Business, 2022)
Online shopping has become an integral part of our daily lives as it is more convenient and easier to do anywhere and anytime. Perceived risk is one of the major concerns that is widely discussed in past studies in relation to online shopping activities. Though there are huge studies looking into the perceived risk aspect of online shopping, there is still a lack of studies looking into the context of Malaysia and focused on online shopping adoption. Thus, this research aims to examine the relationship between perceived risk and online purchase intention in the context of Malaysia. This study has used the Theory of Planned Behavior (TPB), and the Theory of Technology Acceptance Model (TAM) to observe this relationship. This study has used a quantitative research method to gather the data respondents, about 124 questionnaires have been answered among consumer millennials in Batu Pahat, Johor. The structure of the questionnaire based on the self-administrated and the online survey has been applied. All this data is using the software of Statistical Package for Social Science (SPSS) to get the demographic information, variables, and the relationship between perceived risk and online purchase intention. Based on the result for all variables showing a significant relationship of perceived risk and online purchase intention, the highest correlation coefficient between the variables is Psychological Risk which is 0.506. This research can be used for retailers and consumers to gain a better understanding of the perceived risk towards online purchase intention